Influence of Modelling Assumptions on the Seismic Risk of Industrial Precast Concrete Structures - Bressanelli, Michele Egidio; Bellotti, Davide; Belleri, Andrea; Cavalieri, Francesco; Riva, Paolo; Nascimbene, Roberto (Frontiers in Built Environment, 2021)
This research evaluates the influence of different modelling assumptions on the global and local seismic risk assessment of code-conforming precast RC buildings, specifically single-story industrial buildings. In particular the modelling of the system mass, the overhead crane, the beam-to-column and roof-to-beam connections and the cladding system are investigated. For this purpose, a case study resembling a new industrial building designed in accordance with the current Italian building code was selected. Typical dowel beam-to-column connections were considered and the influence of various modelling strategies investigated: perfect hinges, linear elastic connections and non-linear connections with a degrading hysteretic force-displacement model which was calibrated from available data on experimental tests. Three different types of roof-to-beam connections were investigated removing the assumption of rigid diaphragm, namely hot-rolled, cold-formed and socket welded connections. Initially, simplified planar models of single frames were considered to evaluate the influence of the different modelling strategies, then 3D models of the entire building were analyzed. Multiple-stripe non-linear dynamic time history analyses allowed to evaluate displacements, drifts, deformations and ultimate curvatures of the main elements and connections for various intensity measure levels. The seismic risk was assessed in terms of failure rate considering the collapse of both the columns and of the connections. The results show that the beam-to-column connections fail right after reaching yielding due to their low displacement ductility, therefore increasing the collapse rate of the investigated structural typology.